A new multi-neuron spike-train metric - HOUGHTON, CONOR JAMES (MIT Press, 2008)
The Victor-Purpura spike-train metric has recently been extended to a family of multi-neuron metrics and used to analyze spike trains recorded simultaneously from pairs of proximate neurons. The Victor- Purpura metric is one of the two metrics commonly used for quantify- ing the distance between two spike trains, the other is the van Rossum metric. Here, we suggest an extension of the van Rossum metric to a multi-neuron metric. We believe this gives a metric which is both natural and easy to calculate. Both types of multi-neuron metric are applied to simulated data and are compared.
PUBLISHED
Keywords: Pure & Applied Mathematics